Síndrome de DRESS a Lamotrigina em Doente com Melanoma Maligno - Vaz Pinto, Sofia; da Graça, João (Revista Portuguesa de Psiquiatria e Saúde Mental, 2022)
DRESS syndrome (drug reaction with eosinophilia and systemic symptoms) is a rare and severe drug reaction with systemic involvement. We describe a clinical case of a patient diagnosed with malignant melanoma who showed in the emergency room with a generalized morbilliform rash, facial edema and asthenia. The patient had been medicated with pembrolizumab for the last 5 months and had begun lamotrigine for the treatment of a bipolar depression 14 days before the admission. Laboratory tests showed thrombocytopenia, eosinophilia, elevated CRP and abnormal liver function tests. The clinical picture suggested a DRESS syndrome induced by lamotrigin. The drug was discontinued while systemic glucocorticoid treatment was initiated, with complete remission of DRESS symptoms in 30 days. Responsible drug withdrawal is the most important DRESS syndrome treatment measure regarding its major impact on morbidity and mortality outcomes. However, identifying the responsible agent in polymedicated patients is usually a difficult challenge.